The Determinants of SMEs Intention to Adopt Sharia Crowdfunding for Financing Solutions - Alvina, Chintia; Sumardi, Sumardi; Al Azizah, Ummu Salma (EQUILIBRIUM, 2024)
This study aims to identify the variables that influence SMEs' decisions to use sharia crowdfunding in Indonesia as a source of funding. This research focuses on SMEs in Indonesia, which are rarely investigated in the existing literature on sharia crowdfunding. In addition, this study applies the technology acceptance model (TAM), which has not been widely used to identify factors that encourage the adoption of sharia crowdfunding. This study also employs non-probability sampling techniques in conjunction with a quantitative methodology. The data in this study were obtained through a questionnaire survey of 293 respondents obtained from SME owners and managers. The data analysis was conducted using PLS-SEM, while data processing was executed using SmartPLS 3.0. This research assists the government in designing programs and policies to encourage the expansion of SMEs in Indonesia through funding solutions with sharia crowdfunding. Therefore, SMEs have no difficulty in securing funding for their business.